Impact of TiO2, ZnO, and Methylene Blue Doping on the Dielectric anisotropy of planar 8CB nematic liquid crystal - Ocaya, Richard O.; Al-Sehemi, Abdullah G.; Karatas, Sukru; Tataroglu, Adem; Dere, Aysegul; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2024)
In this study, the impact on the dielectric properties of 8CB with the dispersion of TiO2, ZnO, and methylene blue (0% to 5%) is examined. Employing capacitance-voltage (C-V) measurements across frequencies ranging from 10 kHz to 2 MHz, we explore the combined effects of dispersed photoactive nanoparticles and mono/polymeric materials like MB. Our investigation provides novel insights into the nuanced variations induced by transition -metal oxide loaded 8CB, highlighting the role of their oxidation states, and elucidates the influence of larger photoactive monomers on 8CB's dielectric polarizability. The study found that the dielectric anisotropy was strongly influenced by frequency and doping, changing sign at a critical frequency. Our work represents the first comparative analysis incorporating these oxides alongside photoactive materials like MB.
Keywords: Nematic liquid crystals; Dielectric permittivity; Dielectric anisotropy; Frequency switching